Lipid-Associated Macrophages Are Induced by Cancer-Associated Fibroblasts and Mediate Immune Suppression in Breast Cancer - Timperi, Eleonora; Gueguen, Paul; Molgora, Martina; Magagna, Ilaria; Kieffer, Yann; Lopez-Lastra, Silvia; Sirven, Philemon; Baudrin, Laura G.; Baulande, Sylvain; Nicolas, André; Champenois, Gabriel; Meseure, Didier; et al. (Cancer research (Chicago, Ill.), 2022)
Tumor-associated macrophages (TAM) play a detrimental role in triple-negative breast cancer (TNBC). In-depth analysis of TAM characteristics and interactions with stromal cells, such as cancer-associated fibroblast (CAF), could provide important biological and therapeutic insights. Here we identify at the single-cell level a monocyte-derived STAB1+TREM2high lipid-associated macrophage (LAM) subpopulation with immune suppressive capacities that is expanded in patients resistant to immune checkpoint blockade (ICB). Genetic depletion of this LAM subset in mice suppressed TNBC tumor growth. Flow cytometry and bulk RNA sequencing data demonstrated that coculture with TNBC-derived CAFs led to reprogramming of blood monocytes towards immune suppressive STAB1+TREM2high LAMs, which inhibit T-cell activation and proliferation. Cell-to-cell interaction modeling and assays in vitro demonstrated the role of the inflammatory CXCL12-CXCR4 axis in CAF-myeloid cell cross-talk and recruitment of monocytes in tumor sites. Altogether, these data suggest an inflammation model whereby monocytes recruited to the tumor via the CAF-driven CXCL12-CXCR4 axis acquire protumorigenic LAM capacities to support an immunosuppressive microenvironment.Tumor-associated macrophages (TAM) play a detrimental role in triple-negative breast cancer (TNBC). In-depth analysis of TAM characteristics and interactions with stromal cells, such as cancer-associated fibroblast (CAF), could provide important biological and therapeutic insights. Here we identify at the single-cell level a monocyte-derived STAB1+TREM2high lipid-associated macrophage (LAM) subpopulation with immune suppressive capacities that is expanded in patients resistant to immune checkpoint blockade (ICB). Genetic depletion of this LAM subset in mice suppressed TNBC tumor growth. Flow cytometry and bulk RNA sequencing data demonstrated that coculture with TNBC-derived CAFs led to reprogramming of blood monocytes towards immune suppressive STAB1+TREM2high LAMs, which inhibit T-cell activation and proliferation. Cell-to-cell interaction modeling and assays in vitro demonstrated the role of the inflammatory CXCL12-CXCR4 axis in CAF-myeloid cell cross-talk and recruitment of monocytes in tumor sites. Altogether, these data suggest an inflammation model whereby monocytes recruited to the tumor via the CAF-driven CXCL12-CXCR4 axis acquire protumorigenic LAM capacities to support an immunosuppressive microenvironment.This work identifies a novel lipid-associated macrophage subpopulation with immune suppressive functions, offering new leads for therapeutic interventions in triple-negative breast cancer.SIGNIFICANCEThis work identifies a novel lipid-associated macrophage subpopulation with immune suppressive functions, offering new leads for therapeutic interventions in triple-negative breast cancer.